Media konvensional vs media daring: Belajar dari kasus acara Tonight Show – NET TV (Faculty of Communications Science, Dr. Soetomo University, 2020)
The world in one hand, now is no longer just an advertising tagline. It really has become a reality, when the gadget in our hands is able to present all the information needs of the entire world. Not just information, various entertainment can also be found in gadgets. From movies, music, drama series, talk shows, comedy, and various shows owned by influencers or YouTubers that are entertainment. And special, the audience in gadgets only watch the shows they like. There's no way they would waste their quota to watch a program they don't like. The question is, did television audiences still have an audience in such an era? As we all know, television viewers cannot just watch what they like, because in the program they are watching, it is likely that other programs that they dislike (such as advertisements) are tucked away. This paper tries to reveal, is it true that online media can replace conventional media? Or is it true that conventional media has been abandoned by the audience? The results of this study revealed that not all viewers left conventional media. Similarly, not all programs can be enjoyed online. Keywords: Conventional Media; Online Media; The audience.